Tennis for experienced players - Gensemer, Robert E. (Morton Pub. Co., 1994)
This second edition is written for the advanced tennis course participant who wants to improve their skills and play a game of powerful, expressive tennis. It has a no-nonsense approach to the game in a highly readable form which allows the student to easily understand and what is being said and be able to take that knowledge to the court